2021
DOI: 10.1186/s12872-021-02040-3
|View full text |Cite
|
Sign up to set email alerts
|

Significances of viable synergistic autophagy-associated cathepsin B and cathepsin D (CTSB/CTSD) as potential biomarkers for sudden cardiac death

Abstract: Background The Cathepsins family, including cathepsin B and cathepsin D, potentially affects the entire processes involved in atherosclerosis. Although coronary heart disease (CHD) has been widely studied as the basis of Sudden Cardiac Death (SCD), the relationship between CHD and CTSB/D remains unclear. Methods We screened for differentially expressed proteins (DEPs) associated with autophagy by limma package in R. For the genes corresponding to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“… 34 It has been argued that the expression levels of CTSB which was associated with autophagy was upregulated in coronary heart disease tissues. 35 In the CTSB knockout mice, the susceptibility to attenuated enterovirus infection, replication, and disease of food restriction (FR) required functional autophagy and lysosomal biogenesis was blunted. 36 It was reported that elevated blood sugar and obesity are recognized risk factors for atherosclerotic diseases.…”
Section: Discussionmentioning
confidence: 99%
“… 34 It has been argued that the expression levels of CTSB which was associated with autophagy was upregulated in coronary heart disease tissues. 35 In the CTSB knockout mice, the susceptibility to attenuated enterovirus infection, replication, and disease of food restriction (FR) required functional autophagy and lysosomal biogenesis was blunted. 36 It was reported that elevated blood sugar and obesity are recognized risk factors for atherosclerotic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that LXN (latexin) [84], LMNA (lamin A/C) [85], PFKFB3 [86], NEU1 [87], TBK1 [88], GRN (granulin precursor) [89], CTSD (cathepsin D) [90], ACADS (acyl-CoA dehydrogenase short chain) [91], IRF7 [92], S1PR1 [93], ZAP70 [94], IDH1 [95], IL15 [96], PIK3R1 [97], OSM (oncostatin M) [98], SOCS3 [99], USP21 [100], CEP19 [101], KDM2A [102], TP53 [103], BRD2 [104], ATP6 [105], BRD4 [106], COX2 [107], RPS6 [108], ND2 [109], CYTB (cytochrome b) [110] and COX1 [111] are altered expressed in obesity. Altered expression of BCL3 [112], TRAF2 [113], NEU1 [114], SNAP29 [115], AGPAT2 [116], LPCAT3 [117], ADORA2B [118], CTSD (cathepsin D) [119], ACADS (acyl-CoA dehydrogenase short chain) [120], ACAD9 [121], E4F1 [122], IRF7 [123], TAF1 [124], S1PR1 [125], RASSF1 [126], ELAC2 [127], RNF146 [128], COX15 [129], SMYD2 [130], IDH1 [131], MTO1 [132], IL15 [133], PIK3R1 [134], ASB1 [135], OSM (oncostatin M) [136], ZNF791 [137], GBA (glucosylceramidase beta) [138], SOCS3 [139], SLC39A7 [140], AKIP1 [141], AMIGO2 [142], GLUL (glutamate-ammonia ligase) [143], SEMA4D [144], KDM2A [145], TP53 [146], JARID2 [147], CTBP1 [148], ATP6 [149], RPL7 [150], HSP90AA1 [151], BRD4 [152], PSMB4 [153], COX2 [154], JUND (JunD proto-oncogene, AP-1 transcription factor subunit) [155], RPS5 [156], RACK1 […”
Section: Discussionmentioning
confidence: 99%
“…Pathways include metabolism [ [89], CTSD (cathepsin D) [90], ACADS (acyl-CoA dehydrogenase short chain) [91], IRF7 [92], S1PR1 [93], ZAP70 [94], IDH1 [95], IL15 [96], PIK3R1 [97], OSM (oncostatin M) [98], SOCS3 [99], USP21 [100], CEP19 [101], KDM2A [102], TP53 [103], BRD2 [104], ATP6 [105], BRD4 [106], COX2 [107], RPS6 [108], ND2 [109], CYTB (cytochrome b) [110] and COX1 [111] are altered expressed in obesity. Altered expression of BCL3 [112], TRAF2 [113], NEU1 [114], SNAP29 [115], AGPAT2 [116], LPCAT3 [117], ADORA2B [118], CTSD (cathepsin D) [119], ACADS (acyl-CoA dehydrogenase short chain) [120], ACAD9 [121], E4F1 [122], IRF7 [123], TAF1 [124], S1PR1 [125], RASSF1 [126], ELAC2 [127], RNF146 [128], COX15 [129], SMYD2 [130], IDH1 [131], MTO1 [132], IL15 [133], PIK3R1 [134], ASB1 [135], OSM (oncostatin M)…”
Section: Discussionmentioning
confidence: 99%
“…It was found that cathepsin B participates in the conversion of proinsulin to insulin. It is also involved in some diabetic complications, including CVD [148,149]. The downregulation of CTSB suppresses autophagy and promotes apoptosis contributing to the development of proliferative diabetic retinopathy [150].…”
Section: Ctsb-related Networkmentioning
confidence: 99%